A Mechanistic Site-Of-Action Model: A Tool for Informing Right Target, Right Compound, And Right Dose for Therapeutic Antagonistic Antibody Programs - Kapitanov, Georgi I.; Chabot, Jeffrey R.; Narula, Jatin; Roy, Mahua; Neubert, Hendrik; Palandra, Joe; Farrokhi, Vahid; Johnson, Jay S.; Webster, Robert; Jones, Hannah M. (Frontiers in Bioinformatics, 2021)
Quantitative modeling is increasingly utilized in the drug discovery and development process, from the initial stages of target selection, through clinical studies. The modeling can provide guidance on three major questions – is this the right target, what are the right compound properties, and what is the right dose for moving the best possible candidate forward. In this manuscript, we present a site-of-action modeling framework which we apply to monoclonal antibodies against soluble targets. We give a comprehensive overview of how we construct the model and how we parametrize it and include several examples of how to apply this framework for answering the questions postulated above. The utilities and limitations of this approach are discussed.